An exploratory study on Kuala Lumpur commodity exchange and its mechanism / Roziati Hani Ismail - Ismail, Roziati Hani (1992)
A feasibility study to introduce futures trading market in Kuala Lumpur has been conducted by the Government since 1970s. At that time, the prices of commodities for example Crude Palm Oil (CPO) and cocoa were determined by outside buyers or consumers in London and Rotterdam futures market. Interested parties started to raise questions. Why not us, as the producers of the said commodities set the prices? Why must outside people determine the prices of our commodities, the product of our country? These questions formed an idea that is to make Kuala Lumpur as an establish center for commodities trading. With that in mind, Kuala Lumpur Commodity Exchange was incorporated on 23 October 1980. This incorporation was commented in an article Fulfilling Need For Futures Market published by News Straits Time dated 5 August 1988.